Odyssea - Homer (Bibliotheca scriptorum Graecorum et Romanorum Teubneriana ;, 2017)
No existing edition of the Odyssey provides users with adequate information about the readings of the best manuscripts or about the indirect tradition. This new one, designed to stand beside the author?s existing edition of the Iliad (BT 1998-2000), aims to meet the need. The Prolegomena include a comprehensive survey of doubtful points of Homeric orthography in the light of modern linguistic knowledge. The text is based on fresh collations of selected medieval manuscripts and makes use of over 500 papyrus fragments (more than half of them unpublished), with a careful reappraisal of all questions arising. Below the text there appear an extensive register of testimonia and a detailed critical apparatus. The volume is completed by an index of names. This is likely to be the standard edition of reference for decades to come.